Cultural Consonance, Religion and Psychological Distress in an Urban Community - Dressler, William W.; Dengah II, H. J. Francois; Balieiro, Mauro Campos; Santos, Jose Ernesto dos (Paidéia (Ribeirão Preto), 2013)
Cultural consonance is the degree to which individuals approximate prototypes encoded in cultural models. Low cultural consonance is associated with higher psychological distress. Religion may moderate the association between cultural consonance and psychological distress. Brazil, with substantial variation in religion, is an important society for the examination of this hypothesis. Research was conducted in Ribeirão Preto, Brazil, using a mixed-methods design. Measures of cultural consonance were derived using ethnographic methods and then applied in a survey of 271 individuals drawn from four distinct social strata. Low cultural consonance was associated with higher psychological distress in multiple regression analysis ( B = -.430, p < .001). Members of Pentecostal Protestant churches reported lower psychological distress independently of the effect of cultural consonance ( B = -.409, p < .05). There was no buffering effect of religion. Implications of these results for the study of religion and health are discussed.